2018
DOI: 10.2217/cns-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Shadow study: randomized comparison of clinic with video follow-up in glioma undergoing adjuvant temozolomide therapy

Abstract: Aim:This study was designed with a primary objective to study the rate of agreement in treatment plan and decisions between video follow-up (VF) and conventional clinic follow-up (CF).Patients & methods:Adult patients with intermediate- to high-grade glioma on adjuvant temozolomide (TMZ) with facilities for live video call were invited to participate in the study.Results:The concurrence in decision of administering TMZ between VF and CF was 100% (p < 0.00). The median cost incurred in VF was US$58.15 while tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Patil et al 44 evaluated feasibility and safety of video clinic reviews for 65 adults with glioma (II‐IV) who had completed ≥2 cycles of adjuvant temozolomide. All received conventional (in‐person) follow‐up initially and then video follow‐up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patil et al 44 evaluated feasibility and safety of video clinic reviews for 65 adults with glioma (II‐IV) who had completed ≥2 cycles of adjuvant temozolomide. All received conventional (in‐person) follow‐up initially and then video follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, participants with high levels of adherence, or those completing the intervention typically reported high levels of acceptability or satisfaction ( M = 81%) irrespective of the mode of communication 40,43,44,48–52 . In the only study to compare mode of delivery, Patil et al 44 found that the level of satisfaction with video clinic follow‐up (extremely satisfied = 80%) was comparable to conventional face‐to‐face follow‐up (extremely satisfied = 86%). Furthermore, video follow‐up was associated with less than half the costs of conventional follow‐up, which is likely to be a key consideration for implementation in practice 57 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important consideration is that patients with limited resources or living in remote areas might not have access to such centers of excellence. Potential solutions include referrals for expert consultation with care provided in collaboration with local providers, in person, or via telehealth medicine, 18,19 and the implementation of web-based tumor boards 20,21 to review such cases and provide multidisciplinary expert advice. One important component of achieving the goal of referring adults with medulloblastoma to centers of excellence is to educate patients, caregivers, healthcare providers, and thirdparty payers about the benefits of being seen at centers with expertise.…”
Section: Facilitate Referral To Specialized Centers or "Centers Of Exmentioning
confidence: 99%